Early Bilateral Corneal Ectasia after Photorefractive Keratectomy with Non Identifiable Preoperative Risk Factor: A Case Report - Farhan Khashim Alswailmi; Mujeeb Ur Rehman Parrey (Journal of Clinical and Diagnostic Research)
Corneal ectasia following Photorefractive Keratectomy (PRK) remains a relatively rare but significant complication; however, its onset can range from a few weeks to many years. This case report presents the earliest known onset of bilateral corneal ectasia after PRK in the absence of predictable preoperative risk factors. A 21-year-old male with stable refraction and no family history of keratoconus underwent an uneventful PRK for myopic astigmatism. Despite normal preoperative corneal tomography, bilateral ectasia was diagnosed within one week after surgery. This case emphasises the potential for rapid onset of corneal ectasia following PRK and highlights the importance of patient counseling regarding this early complication.